(untitled) (Research, Society and Development, 2021)
Acetaminophen (N-acetyl-p-aminophenol, APAP) is the most popular drug recommended and consumed for relieving mild and moderate pain and fever. Although effective in therapeutic doses, APAP overdose induces hepatotoxicity, causing acute liver failure. In this study, the hepatoprotective effects and the underlying mechanisms of Lavandula officinalis essential oil (LEO) were investigated in APAP-induced hepatotoxicity. To evaluate the hepatoprotective effect, Balb /c mice were pretreated with LEO at doses of 200 and 400 mg/kg, once daily for seven days. On the seventh day, mice were treated with APAP (250 mg/kg) to induce hepatotoxicity. LEO significantly decreased serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and gamma-glutamyl transferase (γ-GT) compared to the APAP group. Besides, a decrease in myeloperoxidase (MPO) activity, nitric oxide (NO), and pro-inflammatory cytokines levels were observed in liver samples of the LEO treated mice. Moreover, pretreatment with LEO showed significant antioxidant activity by decreasing the levels of malondialdehyde (MDA), carbonylated proteins, reactive oxygen species (ROS), and glutathione (GSH), in addition to increasing levels of the hepatic superoxide dismutase (SOD), catalase (CAT), and oxidized glutathione (GSSG). Our results showed that LEO improved liver functions altered by APAP by inhibiting oxidative stress and inflammatory induced by APAP and other oxidative stress-mediated toxicities.